2017
DOI: 10.3892/ol.2017.6853
|View full text |Cite
|
Sign up to set email alerts
|

Role of 5‑Aza‑CdR in mitomycin‑C chemosensitivity of T24 bladder cancer cells

Abstract: Abstract. Chemotherapeutic insensitivity is one of key obstacles to effectively treating muscle invasive bladder cancer. 5-Aza-2'-deoxycytidine (5-Aza-CdR) has been identified as a tumor suppressive agent in various types of cancer. The aim of the present study was to identify the effects of 5-Aza-CdR on the mitomycin-C (MMC) chemosensitivity of T24 bladder cancer cells and investigate the underlying mechanisms. T24 cells were treated with a combination of MMC and 5-Aza-CdR at various concentrations. The rates… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 21 publications
(20 reference statements)
0
5
0
Order By: Relevance
“…Zhang et al. 52 put forward that 5-Aza-2′-deoxycytidine (5‑Aza‑CdR) increased the effect of mitomycin-C (MMC) on bladder cancer cells via autophagy inhibition; therefore, co-treatment with 5‑Aza‑CdR and MMC resulted in increased apoptosis and cell death.…”
Section: Survival Effects Of Autophagy On Bladder Cancer Cellsmentioning
confidence: 99%
“…Zhang et al. 52 put forward that 5-Aza-2′-deoxycytidine (5‑Aza‑CdR) increased the effect of mitomycin-C (MMC) on bladder cancer cells via autophagy inhibition; therefore, co-treatment with 5‑Aza‑CdR and MMC resulted in increased apoptosis and cell death.…”
Section: Survival Effects Of Autophagy On Bladder Cancer Cellsmentioning
confidence: 99%
“…MMC is acting as an linking agent for adverse biological action to another in the cell. For the adverse biological action, MMC is associated with apoptosis stimulation, mutagenesis, and suppression of DNA synthesis (Boamah et al, 2007;Mao, Varoglu, & Sherman, 1999;Zhang, Huang, Cao, Li, & Xu, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Further investigation revealed that the autophagy inhibitor ROC-325 improved the anti-leukemic action of azacitidine in acute myeloid leukemia cells [42]. Interestingly, detacibine, an analogue of azacitidine, had a similar effect, as it induced autophagy of cancer cells, including UBUC cells [43,44]. The autophagy-inducing effect of detacibine was observed in mouse neuronal cell lines, which also showed increased hypoxia tolerance following detacibine treatment.…”
Section: Discussionmentioning
confidence: 98%